Effects of cobalt substitution on structure and microwave absorption properties of PrNi5 alloy - 潘顺康 熊吉磊 成丽春 姚青荣 饶光辉 (Journal of rare earths, 2015)
The polycrystalline samples PrNi5_xCox （x=0.0, 0.1, 0.2, 0.3, 0.4） were synthesized by arc smelting and high energy ball milling method. The phase structure, morphology, saturation magnetization and electromagnetic parameters of the alloy powders were characterized by X-ray diffraction （XRD）, scanning electron microscopy （SEM）, vibrating sample magnetomctry （VSM） and vector network analyzer （VNA）, respectively. The results revealed that the lattice parameter a and c and unit-cell volume V increased with the increasing amount of Co substitution. The saturation magnetization increased as Co content increased. The minimum absorp- tion peak frequency shifted towards lower frequency region with the increasing amount of Co substitution. And the minimum reflec- tion loss of the PrNi5 xCox powders increased first and then decreased with the increasing amount of Co substitution. The PrNisCox alloys possessed the excellent microwave absorbing properties. The minimum reflection loss of the PrNi4.gCo0,1 alloy all could reach 20.0 all3 with the coating thickness ranging from 1.8 to 3 ram. The minimum reflection loss of PrNi4.gCoo.l powders was -36.20 d13 at 7.76 GHz, and the frequency bandwidth ofR〈10 dB reached about 1.50 GHz with the best matching condition d=2.0 ram.